A to Z: Current Spinal Cord Injury Rehabilitation - Jony Sieman; Mohammad Yusof Ibrahim; Liew, Constance Sat Lin (2018)
Over the past century, the remarkable advances in health care have changed the outlook on Spinal Cord Injury (SCI). The “grim prognosis” has become a story of the past, and today, the life expectancy of the SCI survivors has been comparable to that of general population, and the health care providers are working harder to improve quality of life of SCI patients, whilst various ongoing research are promising for a better healing potentials. At this moment, resources, management strategies and policies are important factors that must be properly managed to further improve the SCI outcomes. As a newcomer, the telerehabilitation system promises to resolve issues on unmet medical needs, financial and manpower constraints, rehabilitation interventions and independence of activities of daily living.